F-105 Vesiculovirus vectored vaccines can provide single dose protection against filoviruses, arenaviruses, and alphaviruses. (March 2017) - Fouts, Timothy
Abstract : Demetrius Matassov, PhD; Stefan Hamm, PhD; Terri Latham, BS; Becky Nowak, BS; Cheryl Kotash, BS; Daniel Colon; BS; Susan Witko, BS; Luke Jasenosky, BS; Rong Xu, PhD; Ayuko Ota-Setlik, BS; Michael Egan, PhD; David Clarke, PhD; John Eldridge, PhD. The Vesiculovirus genus, family Rhabdoviridae, is composed of negative-sense single-stranded RNA viruses. Jack Rose pioneered the development of these viruses as a vaccine platform using vesicular stomatitis virus (VSV) to express antigens from a variety of viral, protozoan, and bacterial pathogens. Further developed by Profectus BioSciences, the VesiculoVaxTM vector platform is unlike adenovirus and other viral vectors as there is little pre-existing immunity that would limit vaccine take. Multiple clinical trials have shown that attenuated recombinant VSV (rVSV) vectors are safe and immunogenic in humans across a range of doses. VesiculoVaxTM vectors are replication-competent, and have inherent adjuvant properties that activates innate immunity and efficiently primes and expandes B cells to antibody-producing cells. This capability enables the development of prophylactic vaccines that amplify pathogen specific B-cell immune response(s) resulting in rapid induction of neutralizing antibodies and protection from disease. VesiculoVaxTM based vaccines protected non-human primates against hemorrhagic fever viruses such as Ebola, Marburg, and Lassa, and is the only vaccine to have demonstrated single-dose protection of monkeys against lethal challenge with highly virulent, low-passage Ebola and Marburg viruses. VesiculoVaxTM based vaccines also protected animals against chikungunya virus as well as the Western, Eastern, and Venezuelan equine encephalitic alphaviruses. An attenuated rVSV-Ebola vaccine vector has now completed enrollment in a phase 1 clinical trials. These results demonstrate that vesiculovirus vectors have tremendous potential as vaccines for protection against a wide range of acute viral infections.